2002
DOI: 10.1523/jneurosci.22-23-10501.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Cerebral and Cerebellar Cortex by Auditory Stimulation at 40 Hz

Abstract: We used functional brain imaging with positron emission tomography (PET)-H 2 15 O to study a remarkable neurophysiological finding in the normal brain. Auditory stimulation at various frequencies in the gamma range elicits a steady-state scalp electroencephalographic (EEG) response that peaks in amplitude at 40 Hz, with smaller amplitudes at lower and higher stimulation frequencies. We confirmed this finding in 28 healthy subjects, each studied with monaural trains of stimuli at 12 different stimulation rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
138
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(164 citation statements)
references
References 40 publications
11
138
2
Order By: Relevance
“…Because imaging studies explicitly manipulating cognitive, emotion, or motor confounds were specifically excluded from this study, cerebellar activation also did not depend on variations in these conditions. Although the relatively few neuroimaging studies intended specifically to examine cerebellar auditory responses have designed their tasks to focus on one or another hypothesized specific function [e.g., timing: Ackermann et al, 2001;Pastor et al, 2002;speech processing: Mathiak et al, 2002;, our data suggest that the revealed cerebellar activations are more likely related to the general processing of auditory stimuli. This is the kind of result that can be revealed most clearly by a meta-analysis of multiple published studies.…”
Section: Response Patterns In the Cerebellummentioning
confidence: 72%
See 2 more Smart Citations
“…Because imaging studies explicitly manipulating cognitive, emotion, or motor confounds were specifically excluded from this study, cerebellar activation also did not depend on variations in these conditions. Although the relatively few neuroimaging studies intended specifically to examine cerebellar auditory responses have designed their tasks to focus on one or another hypothesized specific function [e.g., timing: Ackermann et al, 2001;Pastor et al, 2002;speech processing: Mathiak et al, 2002;, our data suggest that the revealed cerebellar activations are more likely related to the general processing of auditory stimuli. This is the kind of result that can be revealed most clearly by a meta-analysis of multiple published studies.…”
Section: Response Patterns In the Cerebellummentioning
confidence: 72%
“…Despite having been confirmed repeatedly across different animal species [Aitikin and Boyd, 1975;Huang and Liu, 1990;Sun et al, 1983;Wolfe and Kos, 1975;Xi et al, 1994], we know of no positron emission tomography (PET) or functional magnetic resonance imaging (fMRI) studies that have tested specifically for a purely sensory role for the cerebellum in auditory processing. Instead, most studies have focused on higherlevel aspects of auditory processing, such as the timing and duration of sounds for speech perception [Mathiak et al, 2002[Mathiak et al, , 2004, processing of stimuli presentation rate [Ackermann et al, 2001;Pastor et al, 2002], or perceptual timing in general [Jueptner et al, 1995;Mangels et al, 1998;Nichelli et al, 1996]. Again, our hypothesis posits that cerebellar involvement in audition is more fundamental, operating at the level of the basic mechanisms of active auditory sensory data acquisition.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this case, visual flashes, or auditory tones, are presented at different rates, and the stimulation frequency that results in the largest EEG or magnetoencephalography output, the resonance frequency, is detected. This standardized approach yielded consistent results and demonstrated the existence of clear-cut resonance frequencies in specific parts of the human corticothalamic system, ϳ10 Hz (Narici and Romani, 1989;Regan, 1989;Silberstein, 1995;Rager and Singer, 1998;Herrmann, 2001) in visual cortex and ϳ40 Hz in auditory cortex (Galambos et al, 1981;Pastor et al, 2002). However, steady-state responses, as other responses evoked by the stimulation of peripheral receptors, can only probe a limited set of primary sensory cortices.…”
Section: Introductionmentioning
confidence: 71%
“…Such entrainment of auditory cortical neurons can be recorded by noninvasive methods such as electroencephalography (EEG) and is termed auditory steady-state response (ASSR). In humans, the scalp-recorded ASSR is maximal when auditory stimuli are delivered at ∼ 40 Hz (Galambos et al, 1981;Pastor et al, 2002) and appears to reflect resonance frequency of the underlying neural circuits (Llinas, 1988;Llinas et al, 1991;Rosanova et al, 2009). A key part of the circuitry responsible for entrainment to exogenous stimuli appears to involve parvalbumin-positive (PV+), GABAergic basket interneurons and the pyramidal cells of the upper layers of the sensory cortex (Cardin et al, 2009;Carlen et al, 2012;Sohal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%